Narrativisation of the Mau Mau Rebellion in Ngugi wa Thiong’o’s Weep Not, Child - Thakur, Ram Sebak; Singh, Ajita (Nepal Journal of Multidisciplinary Research, 2025)
Background and Aim: Ngugi wa Thiong'o's seminal novel Weep Not, Child (1964) chronicles the historical experience of Kenya, foregrounding the historical, political, and socio-economic occurrences during the colonial rule in the country. The novel juxtaposes some historical incidents of Kenya in a fictionalised fashion to show the Kenyan people's resistance to white domination and its aftermaths. Thiong'o's reference to the Mau Mau rebellion against the colonizers and those Kenyan people collaborating with them is dealt with great care in the novel. In order to underscore this theme of resistance against the deeply entrenched oppressive power structures, Thiong'o has his characters like Kamau, Boro and several others who take oaths and enroll in the Mau Mau movement to fight for cultural freedom, land acquisition, and national independence. But the question is: what is the outcome of this movement and what impact does it have on the life of the colonisers and the colonised? The purpose of this paper is to explore and excavate the answer of these questions. Put differently, the paper attempts to glean the profound impact of Mau Mau movement both on the colonisers and the colonised, ultimately disrupting colonial Kenya's social, political, and familial structures through the analysis of resistance, violence, and disillusionment. Methods: This study combines a qualitative research approach and a historical framework to accomplish the objective of the research. The narratives and anecdotes in the novel are analysed and contextualised with reference to the historical incidents of the then Kenya. Results: The novel is a powerful reaction against the economic disparities prevalent in the country, land confiscation by the white settlers, and the exploitation and violence meted upon the local in the name of maintaining law and orders. Thiong'o mightily vocalises resistance against the white settlers by annunciating their barbarity to the black people. Conclusion: Ngũgĩ wa Thiong’o's Weep Not, Child is a powerful literary representation of the Mau Mau rebellion, shedding light on its causes, impact, and significance. Through a rich tapestry of characters and themes, the novel provides a nuanced exploration of colonial oppression, resistance, and the price of freedom. By capturing the historical realities of the Mau Mau struggle, Ngũgĩ not only preserves the memory of Kenya’s fight for independence but also offers insights into the ongoing challenges of post-colonial identity and justice. Novelty: This study contributes to literary scholarship by offering a detailed analysis of how Ngũgĩ's novel constructs a counter-narrative to the European settlers' biased representation of the Mau Mau, interrogating its misrepresentation and re-establishing it as a politically coherent movement for independence.